Q: -10 x -1

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

easiest way of explaining it is as follows 103 = 1 x 10 x 10 x 10 102 = 1 x 10 x 10 101 = 1 x 10 100 = 1

f(x) = x^2 - 9x - 10 = ( x - 10 ) ( x + 1 )Answer : ( x - 10 ) ( x + 1 )

1 x 10 to the power of 2 is 1 x 102 or 10 x 10 or 100

10% of 10 is One 10 x 10/100 = 10 x 1/10 = 10/10 = 1

2 x 5 x 10 - 1= n 10 x 10 - 1=n 100 - 1 =n 99= n

Related questions

1 x 101 = 10 1 x 100 = 1 1 x 10-1 = 0.1 1 x 10-2 = 0.01 1 x 10-3 = 0.001 1 x 10-4 = 0.0001 1 x 10-5 = 0.00001 1 x 10-6 = 0.000001 1 x 10-7 = 0.0000001 1 x 10-8 = 0.00000001 1 x 10-9 = 0.000000001 1 x 10-10 = 0.0000000001

easiest way of explaining it is as follows 103 = 1 x 10 x 10 x 10 102 = 1 x 10 x 10 101 = 1 x 10 100 = 1

f(x) = x^2 - 9x - 10 = ( x - 10 ) ( x + 1 )Answer : ( x - 10 ) ( x + 1 )

first you forget the 2 is there. then you go : 1/10 x 1/10 x 1/10 x 1/10 x 1/10 x 1/10 = b now make b a 2. 2 x 10 -6 is 0.000002.

1 x 10 to the power of 2 is 1 x 102 or 10 x 10 or 100

10% of 10 is One 10 x 10/100 = 10 x 1/10 = 10/10 = 1

1,874,161 = (1 x 10^6) + (8 x 10^5) + (7 x 10^4) + (4 x 10^3) + (1 x 10^2) + (6 x 10^1) + (1 x 10^0)

With and without exponents:(1 x 10^8) + (0 x 10^7) + (3 x 10^6) + (7 x 10^5) + (2 x 10^4) + (1 x 10^3) + (4 x 10^2) + (9 x 10^1) + (5 x 10^0)(1 x 100000000) + (0 x 10000000) + (3 x 1000000) + (7 x 100000) + (2 x 10000) + (1 x 1000) + (4 x 100) + (9 x 10) + (5 x 1)

2 x 5 x 10 - 1= n 10 x 10 - 1=n 100 - 1 =n 99= n

The answer is A 1 x 10^(-6)

2 x 10^1 x 1 x 10^5 = 2 x 10^6

5 x -2 = -10